Growing Potatoes in the Florida Home Garden - Christian T. Christensen; Libby R. Rens; Jeffrey E. Pack; Lincoln Zotarelli; Chad Hutchinson; Wendy Dahl; Doug Gergela; James M. White (EDIS)
The Irish potato is a cool-season crop. A recently grown and harvested potato exhibits different flavor profiles from one that has been in storage or on a grocery shelf for an extended period. For example, in storage, the starches in potatoes convert to sugars, resulting in a less desirable texture and taste. “New” potato flavor can be achieved in the home garden by following a few growing recommendations. This 9-page fact sheet was written by Christian T. Christensen, Libby R. Rens, Jeffrey E. Pack, Lincoln Zotarelli, Chad Hutchinson, Wendy Dahl, Doug Gergela, and James M. White, and published by the UF Department of Horticultural Sciences, April 2013.